Analysis of prescribing error incidence in out-patient prescription at community health center of Tilamuta Boalemo Regency - Sukmawati Damiti; Syamsul Thalib; Vyani Kamba; Ysrafil Ysrafil; Hartati Hartati (Institute of Computer Science (IOCS), 2022)
Prescribing error can also be referred to as the error in medicine prescription that could endanger the patients. The absence of the right preparation dose can be potentially lead to misread by the transriber, as different medicines might have various preparation doses. The aimed of this study to identify the prescribing errors cases in patients in Tilamuta Community Health Center. The analysis on the prescription was conducted to identify the administrative and pharmaceutical completeness of the prescription. The data involved retrospective and prospective towards 300 prescriptions of out patients in Tilamuta Community Health Center by random sampling Method. The inclusion criteria employed out patient prescription for patients age 1-15 years old and 60 years old and above. The results showed that the highest percentage of prescribing error cases was in administrative error at 98,3% (295 prescription), while in the pharmaceutical error, the percentage arrived at 52,3% (157 prescription). This study was concluded that the highest prescribing error cases in Tilamuta community Health Center were the administrative error in the form of the absence of Occupational License at 96,7% or 293 prescriptions, while the pharmaceutical error at 37,3% or 112 prescriptions involved too low dosage.